IMPLEMENTASI METODE SIMPLE ADDITIVE WEIGHTING (SAW) PADA SISTEM KEPUTUSAN PENENTUAN PENERIMA BANTUAN BEDAH RUMAH DI KECAMATAN PULO BANDRING - Zunaida Sitorus (JURNAL PIONIR, 2020)
Pulo Bandring Subdistrict is a sub-district in Asahan Regency, in the prosperity of the community the Pulo Bandring sub-district has a house renovation program that is no longer habitable with this program, which is expected to improve the welfare of its citizens. But the problems that occur in the field when making a decision to determine whether or not a proper house renovation from the government is appropriate and appropriate. Because usually the determination of eligibility is determined by a team appointed by the government, this team determines whether or not they are entitled to get house renovation assistance by the local government. Assessment of whether or not feasible to get the house surgery assistance, still uses the manual method that only looks at aspects that are developing in the community but does not see from the other side and may be a decision making there are weaknesses in it, so from that the compiler thinks and makes a a system that can determine the feasibility of a home surgical recipient to be more efficient and no longer uses a manual system so that the home surgical recipient is right on target. Decision Support System is a tool that serves to determine whether or not the public gets a house renovation from the right and proper government. Because the system can determine the feasibility of a home surgery recipient to be more efficient and no longer use a manual system so that the recipient of home surgery is right on target and in accordance with the qualifications that are indeed in need of assistance with house surgery. Keywords: Home Surgery, SAW, Decision Support System, Web